2005
DOI: 10.1287/orsc.1040.0107
|View full text |Cite
|
Sign up to set email alerts
|

How Much Better Are the Most-Prestigious Journals? The Statistics of Academic Publication

Abstract: Articles in high-prestige journals receive more citations and more applause than articles in less-prestigious journals, but how much more do these articles contribute to knowledge? This article uses a statistical theory of review processes to draw inferences about differences value between articles in more-prestigious versus less-prestigious journals. This analysis indicates that there is much overlap in articles in different prestige strata. Indeed, theory implies that about half of the articles published ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
266
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(281 citation statements)
references
References 53 publications
6
266
0
9
Order By: Relevance
“…in addition to their broad disciplinary appeal, ranking studies have consistently appeared in prestigious journals for a long period of time. examples of these include allison and stewart (1974) in American Sociological Review; Graves et al (1982) in American Economic Review;chung and cox (1990) in Journal of Finance; Tracy and Waldfogel (1997) in Journal of Business;starbuck (2005) in Organization Science; and Mitra and Golder (2008) in Journal of Marketing.…”
Section: Introductionmentioning
confidence: 99%
“…in addition to their broad disciplinary appeal, ranking studies have consistently appeared in prestigious journals for a long period of time. examples of these include allison and stewart (1974) in American Sociological Review; Graves et al (1982) in American Economic Review;chung and cox (1990) in Journal of Finance; Tracy and Waldfogel (1997) in Journal of Business;starbuck (2005) in Organization Science; and Mitra and Golder (2008) in Journal of Marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Starbuck (2005) found that although higher--prestige journals publish more highly cited articles, editorial selection involves considerable randomness. He concluded: "Evaluating articles based primarily on which journal published them is more likely than not to yield incorrect assessments of the articles ' value."…”
Section: The Dutch Economics Top--40mentioning
confidence: 99%
“…Apesar de alguns autores (vide: JUSTICE et al, 1998;HOJAT;GONNELLA;CAELLEIGH, 2003) defenderem que há uma inabilidade de efetivamente dar anonimidade aos pesquisadores mais famosos em suas áreas, esse tipo de revisão tenta fornecer uma imparcialidade para os pareceres, o que se estima contribuir para melhorar a qualidade do processo editorial (LAZAROIU, 2009). Em todo o caso, o processo de avaliação pelos pares não é perfeito e diversas limitações e disfunções têm sido apontadas (STARBUCK, 2005). Entre elas lentidão, dificuldade em detectar fraudes e erros estatísticos, rejeição de novas ideias, possibilidade de plágio, dupla submissão, subjetividade, conservadorismo e favorecimento às redes elitistas (PAVAN; STUMPF, 2009).…”
Section: Revisão Da Literatura Revisoresunclassified